2022
DOI: 10.1002/advs.202105731
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Prevented Stress‐Induced Anxiety via Improving Brain RNA Methylation

Abstract: Physical exercise is effective in alleviating mental disorders by improving synaptic transmission; however, the link between body endurance training and neural adaptation has not yet been completely resolved. In this study, the authors investigated the role of RNA N6‐methyladenosine (m6A), an emerging epigenetic mechanism, in improved resilience against chronic restraint stress. A combination of molecular, behavioral, and in vivo recording data demonstrates exercise‐mediated restoration of m6A in the mouse med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…These studies further implied the possible involvement of cellular events during chronic exercise training. Our recent work has revealed the change of RNA methylation within mPFC-BLA pathway under the same treadmill exercise paradigm on CRS model 36 , providing an alternative molecular explanation for the long-term modification of neural circuit underlying exercise intervention.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These studies further implied the possible involvement of cellular events during chronic exercise training. Our recent work has revealed the change of RNA methylation within mPFC-BLA pathway under the same treadmill exercise paradigm on CRS model 36 , providing an alternative molecular explanation for the long-term modification of neural circuit underlying exercise intervention.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to the neural circuitry mechanism as stated above, exercise may also modulate different kinds of peripheral factors, which further contribute to the central modulation of neural network. Our group recently identified a hepatic-secreted metabolite, S-adenosylmethionine (SAM), to be involved in the RNA methylation of synaptic gene transcripts during chronic treadmill exercise for conferring stress resilience 36 . Another adipocyte-derived molecule, clusterin, has also been found to protect cortical neural network via suppressing neuroinflammation 45 .…”
Section: Discussionmentioning
confidence: 99%
“…m6A-mRNA methylation in the VTA increases in response to CUMS in comparison to unstressed animals [ 138 ]. Yan et al (2022) showed that treadmill exercise in RNA m6A homeostasis in the PFC plays a role by improving the resilience against CRS for one hour for 14 days [ 139 ]. RNA methylation in mPFC neurons depends on methyl donor S-adenosyl methionine (SAM) liver biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Horowitz et al (2020) reported that an elevated concentration of liver-derived glycosylphosphatidylinositol (GPI)-specific phospholipase D1 in the plasma of mice after exercise can improve hippocampal function and alleviate cognitive impairment in elderly mice. Yan et al (2022) found that aerobic exercise increases the synthesis of liver methyl donors, leading to enhanced brain RNA N6-methyladenosine levels and exhibiting anti-anxiety effects. These research findings collectively suggest that liver-derived factors play a significant role in mild cognitive impairment associated with liver disease.…”
Section: Liver-derived Factorsmentioning
confidence: 99%